Gender, Socioeconomic Status, Cultural Differences, Education, Family Size and Procrastination: A Sociodemographic Meta-Analysis - Lu, Desheng; He, Yiheng; Tan, Yu (Frontiers in Psychology, 2022)
Procrastination describes a ubiquitous scenario in which individuals voluntarily postpone scheduled activities at the expense of adverse consequences. Steel (2007) pioneered a meta-analysis to explicitly reveal the nature of procrastination and sparked intensive research on its sociodemographic characteristics. However, conflicting and heterogeneous findings reported in the existing literature make it difficult to draw a reliable conclusion. In addition, there is still room to further investigate more sociodemographic features of procrastination, such as socioeconomic status, cultural differences and education. To this end, we performed large-scale quantitative sociodemographic meta-analyses (total n = 106,764) to fill this gap. Procrastination tendencies were found to be stronger in males than in females (r = .04, 95% CI: .02-.05). No significant effects of differences in socioeconomic status (i.e., poor or rich), multicultures (i.e., Han nation or minorities), nationality (i.e., China or other countries), family size (i.e., one child or > 1 child), and educational background (i.e., science or arts/literature) were found to affect procrastination tendencies. Furthermore, it was noteworthy that the gender differences in procrastination tendencies were prominently moderated by measurements, with greater effects on the Akiten Procrastination Inventory (API) (r = .035, 95% CI: -.01-.08) than on the General Procrastination Scale (GPS) (r = .018, 95% CI: -.01-.05). In conclusion, this study provides robust evidence demonstrating that males tended to procrastinate more than females and further indicates that procrastination tendencies do not vary based on sociodemographic situations, including socioeconomic status, multicultures, nationality, family size, and educational background.